1996
DOI: 10.1073/pnas.93.21.11652
|View full text |Cite
|
Sign up to set email alerts
|

Single residue substitutions that change the gating properties of a mechanosensitive channel in Escherichia coli.

Abstract: MscL is a channel that opens a large pore in the Escherichia coli cytoplasmic membrane in response to mechanical stress. Previously, we highly enriched the MscL protein by using patch clamp as a functional assay and cloned the corresponding gene. The predicted protein contains a largely hydrophobic core spanning two-thirds of the molecule and a more hydrophilic carboxyl terminal tail. Because MscL had no homology to characterized proteins, it was impossible to predict functional regions of the protein by simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
280
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(296 citation statements)
references
References 18 publications
14
280
2
Order By: Relevance
“…4). Two regions of localized conservation were noted, shown previously to encompass transmembrane elements (Blount et al, 1996b). The cytoplasmic ends of these segments, corresponding to the E. coli regions G14-F29 and V72-F85, bear the highest degree of conservation.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…4). Two regions of localized conservation were noted, shown previously to encompass transmembrane elements (Blount et al, 1996b). The cytoplasmic ends of these segments, corresponding to the E. coli regions G14-F29 and V72-F85, bear the highest degree of conservation.…”
Section: Resultsmentioning
confidence: 83%
“…In the direction of translation, the MCS contains one consensus each for XhoI, Not I, Bgl II, Sal I and XbaI. E. coli strain PB104 (Blount et al, 1996b) was used to host the intermediate cloning steps and the expression constructs. Cultures were grown at 37ЊC in Luria-Bertani (LB) medium plus ampicillin (100 g ml ¹1 ).…”
Section: Stock and Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Many studies have been performed using site-directed mutagenesis in order to better understand the structure-function of MscL. [13][14][15][16][17][18][19] One of these studies produced an estimation of the tension-sensing site in MscL using random scanning mutagenesis, where individual hydrophobic AAs facing the lipids were replaced with the hydrophilic AA asparagine to identify any "loss-of-function" mutants lacking mechanosensitivity. 15 As the result, it was found that replacement of one of seven amino residues located at the periplasmic end of the transmembrane helices caused the loss of MscL mechanosensitivity, suggesting that one or some of them may act as a tension sensor in MscL.…”
Section: Introductionmentioning
confidence: 99%
“…MS channels are gated channels that stay in the closed state and open up when there is a tension in the cell membrane (6)(7)(8)(9)(10)(11)(12)(13)(14). The only available crystal structure is that of TbMscL (15), which is a homopentamer, with each monomer composed of a transmembrane domain and a cytoplasmic domain.…”
mentioning
confidence: 99%